Deploying and managing a cloud infrastructure real world skills for the CompTIA cloud+ certification and beyond - Gilani, Zafar; Salam, Abdul (IT professional); Ul Haq, Salman (Sybex, a Wiley brand, 2015)
Annotation Learn in-demand cloud computing skills from industry experts. 'Deploying and Managing a Cloud Infrastructure' is an excellent resource for IT professionals seeking to tap into the demand for cloud administrators. This book helps prepare candidates for the CompTIA Cloud+ Certification (CV0-001) cloud computing certification exam.